Are neighbourhood food resources distributed inequitably by income and race in the USA? Epidemiological findings across the urban spectrum - Richardson, Andrea S (BMJ Group, 2012)
OBJECTIVE: Many recent policies focus on socioeconomic inequities in availability of healthy food stores and restaurants. Yet understanding of how socioeconomic inequities vary across neighbourhood racial composition and across the range from rural to urban settings is limited, largely due to lack of large, geographically and socio-demographically diverse study populations. Using a national sample, the authors examined differences in neighbourhood food resource availability according to neighbourhood-level poverty and racial/ethnic population in non-urban, low-density urban and high-density urban areas. DESIGN: Cross-sectional data from an observational cohort study representative of the US middle and high school-aged population in 1994 followed into young adulthood. PARTICIPANTS: Using neighbourhood characteristics of participants in the National Longitudinal Study of Adolescent Health (Wave III, 2001–2002; n=13 995 young adults aged 18–28 years representing 7588 US block groups), the authors examined associations between neighbourhood poverty and race/ethnicity with neighbourhood food resource availability in urbanicity-stratified multivariable linear regression. PRIMARY AND SECONDARY OUTCOME MEASURES: Neighbourhood availability of grocery/supermarkets, convenience stores and fast-food restaurants (measured as number of outlets per 100 km roadway). RESULTS: Neighbourhood race and income disparities were most pronounced in low-density urban areas, where high-poverty/high-minority areas had lower availability of grocery/supermarkets (β coefficient (β)=–1.91, 95% CI –2.73 to –1.09) and convenience stores (β=–2.38, 95% CI –3.62 to –1.14) and greater availability of fast-food restaurants (β=4.87, 95% CI 2.26 to 7.48) than low-poverty/low-minority areas. However, in high-density urban areas, high-poverty/low-minority neighbourhoods had comparatively greater availability of grocery/supermarkets (β=8.05, 95% CI 2.52 to 13.57), convenience stores (β=2.89, 95% CI 0.64 to 5.14) and fast-food restaurants (β=4.03, 95% CI 1.97 to 6.09), relative to low-poverty/low-minority areas. CONCLUSIONS: In addition to targeting disproportionate fast-food availability in disadvantaged dense urban areas, our findings suggest that policies should also target disparities in grocery/supermarket and fast-food restaurant availability in low-density areas.